Evaluation of the Frequency of Occupational Hazards Among a Group of Iranian General Dentists and its Prevention Criteria - Mehrnaz Karimi Afshar; Reza Faryabi; Marzieh Karimi Afshar; Molook Torabi (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate the frequency of occupational hazards and the criteria for their prevention among Iranian dentists. Material and Methods: This cross-sectional study was conducted on 187 general dentists in Kerman. The data collection tool was a questionnaire including personal information (gender, age, marital status, condition and place and years of employment, and the average of weekly working hours) and a valid and reliable questionnaire of occupational hazards, including 24 questions about occupational hazards (6 domain) and nine questions about criteria for the prevention of the risks of dentistry. The t-test, chi-square, and linear regression were used. Results: 92 (49.2%) were men. The mean and standard deviation of the score of occupational hazards was 27.04±16.21 out of 96, and the criteria of prevention were 22.00±7.28 out of 36. Regression analysis showed significant correlations between single statuses, years of occupational and type of employment, weekly work hours and occupational hazards, participation in occupational injury identification courses, and hepatitis vaccination. In addition, there were significant correlations between gender, age, weekly work hours, and preventive measures. Moreover, 3.2% of dentists were in a high-risk group and 26.2% were weak in preventive measures. Conclusion: A total of 32.6% of dentists are at moderate risk of occupational hazards, and 10.7% meet the prevention criteria properly. It is recommended to hold training classes to identify occupational hazards and the criteria for their prevention among dentists.